Low-cost hydroponics in Elementar School II to promote environmental education and interdisciplinarity (Research, Society and Development, 2022)
This work was based on discussing how low-cost hydroponics can be implemented in Elementary School II for classes from 6th to 9th grade aged 11 to 14 years as a learning space for environmental education, favoring interdisciplinarity. We sought to show the importance of the application of hydroponics as a pedagogical practice in Elementary School II. The methodology used was bibliographic research. According to the research, it was possible to develop a pedagogical proposal using low-cost hydroponics. This proposal can contribute to the development of students' learning capacity in a contextualized way through the integration of all curricular components in an interdisciplinary way, to spread the technology in the community in general, emphasizing the importance of environmental education not only in schools, but in the community as a whole.